Bias and social aspects in search and recommendation : first International Workshop, BIAS 2020, Lisbon, Portugal, April 14, Proceedings /: first International Workshop, BIAS 2020, Lisbon, Portugal, April 14, Proceedings. (2020) - Unknown
No abstract available